Devising a branding model for mega- projects in entertainment, residential, tourism and sport in Iran / Amir Ekhlassi ... [et al.] - Ekhlassi, Amir; Divandari, Ali; Rahmani, Kamal (Universiti Teknologi MARA (UiTM), Malaysia, 2013)
While it seems that there are very few studies on the branding pro- cess for mega-projects in entertainment, residential, tourism and sport, branding is one of the most important factors in these types of projects. We have particularly tried to devise a branding model for these types of projects that corresponds to Persian characteristics. Since in Iran there is no special model in this field, the grounded theory approach was used to hypothesize and outline the aspects of the model. In-depth interviews corresponding to grounded theory were conducted. The main phenomenon is branding process for mega-projects in entertainment, residential, tourism and sport. Causal, contextual, and intervening conditions are all explored, and the results are introduced as an intact model. The primary goal of this research is devising a model for branding these mega projects with respect to the Persian characteristics.